Influência de variáveis dendrométricas e morfométricas da copa no incremento periódico de Araucaria angustifolia (Bertol.) Kuntze, Lages, SC - Costa, Emanuel Arnoni (2011)
The influence of morphometric and dendrometric variables in periodic increase in basal increment area was measured on individual trees of Araucaria angustifolia (Bertol.) Kuntze in Lages, Santa Catarina having as objectives to select a model to estimate the total height, the diameter of the crown, to compare methods for the calculation of crown projection area, to model morphometric relations as a function of diameter and develop a model of periodic basal in area increment. Randomly was chosen 85 trees denominated goal, considering a lower center of class and a maximum diameter 10 cm 80 cm, with an amplitude of 10 cm, and at least eight trees per diameter class. Were measured in the object tree and its competitors, the dendrometric, and morphometric variables and these were classified according to their position in sociological dominant, codominant and dominated. The data processing was performed by SAS statistical software (Statistical Analysis System) version 9.1. For total height, was tested eight models, and for the five crown diameter,was selected the best for social status. It was decided to choose a model that best represent all sociological positions, and then there was the analysis of covariance and adjusting for regression with Dummy variables that described for single model, all social positions. Was evaluated methods for the calculation of crown area by social class, considering the measurement of eight, four and two radius crown. It was made the modeling of relationships for the following morphometric variables: the proportion of the crown, formal crown, degree of slenderness, index of range and index of salience. In the modeling of periodic increment in basal area were related the dendrometric and morphometric variables correlated more with that dummy variables stratified with social classes. Were found 193 dominant trees, 40 codominant and 61 dominated with a total of 294 trees. The total height was estimated by Backman model modified with dummy variables D1 and codominant trees D2 trees dominated by the equation: i i i i i i i ) 2 D ) d (ln( 1816 , 5 ) 1 D ) d (ln( 1863 , 3 2 D 7431 , 17 1 D 4939 , 11 ) d ²( ln 6557 , 2 ) d ln( 8011 , 26 1315 , 45 h = − + − + + − − with a R2 0,6608 aj. = e Syx% = 12,24%. The crown diameter was estimated by linear model with dependent variable transformed by square root and dummy variables to stratify the trees dominated D2 by the equation: dc i = 1,6199 + 0,0342 (d)i − 0,3004 D2i + 0,0113 ((d)D2)i Ù with a R2 0,8353 aj. = e Syx% = 15,47%.The crown projection area with the measurement of four rays can be used in symmetric crown as there is no loss of accuracy. The adjusted models of the morphometric relationships presented variation, however, were significant in the diameter. The growth model in basal area obtained as independent variables: formal crown (FC), the proportion of dominant crown trees for (D8PC), the length of crown to dominant trees (D8CC) and the degree of slenderness (GE), with adjustment of: R2 0,8038 aj. = e precisão de Syx% = 25,77%, being expressed in the equation: i i i i PC 8 D 0586 , 0 CC 8 D 2482 , 0 GE 0878 , 2 FC 2087 , 0 2859 , 1 %) g P LN(I = − + − + .The size of the crown represented by formal crown in different social positions, length and crown ratio of dominant crown trees accounted for 76,21% of the total variation of the model of growth in basal area. The morphometric variables, especially those that characterize the size of the crown, are efficient to describle the periodic basal area increment of araucaria.